Newer bronchopulmonary dysplasia definitions and prediction of health economics impacts in very preterm infants. Issue 2 (24th November 2020) - Kurihara, Chie; Zhang, Lishi; Mikhael, Michel
Abstract: Objective: To compare the abilities of bronchopulmonary dysplasia (BPD) definitions to predict hospital charges as a surrogate of disease complexity. Methods: Retrospective study of infants admitted to the neonatal intensive care unit (NICU) less than 32 weeks gestational age. Subjects were classified according to the Canadian Neonatal Network (CNN), the National Institute of Child Health and Human Development (NICHD) (2018), and Jensen BPD definitions as none, mild (1), moderate (2), or severe (3) BPD. Spearman's correlation was performed to evaluate the association of BPD definitions with health economics outcomes. Results: One hundred and sixty‐eight infants were included with mean birth weight of 1197 g and mean gestational age of 28.4 weeks. More infants were classified as no BPD according to CNN definition (79%) in comparison to NICHD 2018 (64.3%) and Jensen (59.5%) definitions. There were fewer infants as the grade of severity increased for all definitions, this was most linear for Jensen definition with Grade 1 present in 25%, Grade 2 in 12.5%, and Grade 3 in 3%. A stronger correlation with NICU length of stay, NICU hospital charges, NICU charges per day, and first year of life hospital charges was detected for Jensen definition (correlation coefficient of 0.58, 0.66, 0.64, 0.67, respectively) in comparison to CNN and NICHD 2018 definitions ( p < .0001). Conclusion: Jensen BPD definition had the strongest correlation with first year health economics outcomes in our study. Validating recent BPD definitions using population‐based data is imperative to improve family counseling and enhance the designs of quality improvement initiatives and therapeutic research studies targeting patient‐centric outcomes.